Biogas production efficiency of park grass waste using HBT method - Güler, Ahmed Serdar; Üçok, Serdar (International Journal of Agricultural and Biological Engineering, 2025)
The continuous increase in global population intensifies the demand for energy. The growing need for energy has led to the ongoing search for new and renewable alternative energy sources instead of fossil fuels. Biogas energy is one of these renewable energy sources. Significant amounts of grass waste are generated in urban parks, gardens, and roadside landscaping areas. These organic wastes are often left to decay in an uncontrolled manner. Converting these wastes into biogas energy can provide added value in terms of both energy production and waste management. This study aims to determine the chemical properties [crude protein, crude fat, Acid Detergent Fiber (ADF), Neutral Detergent Fiber (NDF), dry matter (DM), and organic dry matter (ODM)] of grass wastes obtained from park gardens and those converted into silage, as well as their specific biogas and methane productions (m3/kg ODM) using the Hohenheim Batch Test (HBT) method. Specific biogas and methane productions were experimentally conducted through the HBT method. The results of the study reveal that the highest protein content (17.49%) was observed in Grass 3, the highest fat content (5.13%) in Silage 1, the highest NDF (68%) and ADF (41%) content in Grass 1, the highest DM (90.92%) content in Grass 2, and the highest ODM (92.59%) content in Silage 2. The average cumulative biogas production values ranged from 0.65 to 0.71 m3/kg ODM, while cumulative methane production values ranged from 0.39 to 0.42 m3/kg ODM. The methane content in biogas varied between 59.01% and 60.19%. There was no statistical difference found among methane, biogas, and methane ratios derived from grass materials and silage. This suggests that either storage method - silaging or drying - can be effectively used without impacting overall biogas or methane productivity. Thus, facilities can choose between silage and dried forms based on convenience, storage requirements, or cost, knowing that both methods will perform equivalently in biogas production. This flexibility provides valuable options for optimizing feedstock management and storage in biogas operations. Key words: grass wastes, grass silage wastes, biogas, methane, HBT method DOI: 10.25165/j.ijabe.20251801.9070 Citation: Güler A S, Üçok S. Biogas production efficiency of park grass waste using HBT method. Int J Agric & Biol Eng, 2025; 18(1): 299–303.